Over-the-counter medicines: Global perspective and Indian scenario - Marathe, PA; Kamat, SK; Tripathi, RK; Raut, SB; Khatri, NP (Journal of postgraduate medicine, 2020)
Patients often approach a pharmacist instead of visiting a doctor for minor ailments such as cough, cold, allergies, pain, fever, acidity, diarrhea, and skin-related conditions. Purchase of specific medicines over the counter is legally recognized in most countries. 'Over-the-Counter (OTC) Medicines' means drugs which are legally allowed to be sold by pharmacists without need for a prescription. The term does not have a legal definition in India. Technically, drugs are OTC unless they are specifically stated as prescription only drugs. OTC drugs allow faster and cheaper access to healthcare; however, their misuse and adverse health effects cause concerns. This article describes concept of OTC medicines and practices in India against the background of globally prevalent regulations and practices. A recognized category of OTC medicines by law, patient awareness programs, and support of pharmacists and pharmaceutical companies are required to optimize the use of OTC medicines in India.